Prevalence of thrombocytopenia among patients with malaria in Ethiopia: a systematic review and metanalysis - Mikiyas Shemelis Achame; Alemu Gedefie; Habtu Debash; Andualem Tesfaye; Keleb Takele Tiruneh; Altaseb Beyene Kassaw (Malaria Journal, 2025)
Abstract Background Thrombocytopenia is a common haematological abnormality in malaria patients that is associated with an increased risk of mortality. Given the endemic nature of malaria in Ethiopia, it is crucial to comprehend the prevalence of thrombocytopenia in this setting to enhance clinical care. Therefore, this study aimed to systematically review and synthesize the available evidence on the prevalence of thrombocytopenia among malaria patients in Ethiopia. Methods This systematic review and meta-analysis reviewed studies on thrombocytopenia prevalence in malaria patients, using databases including PubMed, Google Scholar, EMBASE, African Journals online database, and Hinary. STATA version 17 software was used for statistical analysis. A random-effects model was used to estimate pooled effect sizes. Heterogeneity among the included studies was assessed using Galbraith, Cochran’s Q test, and I2 statistics. Subgroup analysis, sensitivity analysis, and meta-regression were conducted to identify the source of heterogeneity. Publication bias was evaluated using a funnel plot and Egger's test. Results Of the 154 studies identified, 31 that fulfilled the eligibility criteria were included in the meta-analysis consisting of 1173 study participants and 823 thrombocytopenic cases. The pooled prevalence of thrombocytopenia was 70% (95% CI: 63, 77) with significant heterogeneity. Subgroup analysis showed the highest pooled prevalence of thrombocytopenia in the Southern Nations Nationalities and Peoples’ region (78.34%) followed by the Amhara region (69.7%), whereas the lowest prevalence was observed in the Gambella Region (63.4%). The sample size was responsible for the observed heterogeneity among the studies, as indicated by the statistically significant result in the meta-regression analysis (p = 0.001). Conclusion Thrombocytopenia is a frequent abnormality finding among malaria patients in Ethiopia, affecting a substantial percentage of individuals. The high frequency found in this research emphasizes the significance of regular platelet monitoring in the treatment of malaria patients. Further studies are needed to investigate the clinical implications of thrombocytopenia in malaria patients.